WHEN GUSTILO III C AND MESS SCORE 9 TRAUMATIC LOWER LIMB MEETS REPLANTATION: A CASE REPORT OF LOWER LIMB REPLANTATION - Yuan, Lam Hui; Mat Johar, Siti Fatimah Noor; WanFaisham, Nu’manWanIsmail; Wan Azman, Wan Sulaiman (International Journal of Allied Health Sciences, 2021)
Mangled Extremity Severity Score (MESS) has been used for more than twenty years to predict the limb salvageability following severe lower extremity trauma. MESS score of greater or equal to seven has hundred precent predictable value for amputation. Warm ischemic time of more than four to six hours in association with type III Gustilo fracture always end up with primary amputation due to unfavourable outcomes. We present a case of 24-year-old man with a near total amputation of right leg in a traumatic event. After thirteen hours of cold ischemic time with a MESS score of nine, the patient underwent leg replantation under the combined effort of orthopaedic and microsurgery team. The replanted limb survived after several surgical procedures. Functionally, he can ambulate with crutches with well-preserved plantar foot sensation. He is still under our rehabilitation program and follow up. We plan to do secondary operation to achieve better aesthetic and functional outcomes. With a dedicated team and good strategy, replantation for a limb of MESS score more than seven is still salvageable. Keyworks: Replantation, Amputation, Trauma, Microsurgery, Mangled extremities